Human Resource Planning in Educational Quality Improvement - Hermawan Hermawan; Hasyim Asy'ari; Armai Arief (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Human resources play an important role in realizing school goals, so leaders should know how to use human resource planning properly.The purpose of this study is to describe human resource planning, educational quality, and human resource planning in improving the quality of education at 25 Public High School Tangerang. The approaches and methods in this study used descriptive qualitative. Research data collection techniques were carried out through interviews, observation, and document studies. The results of this study describe human resource planning at 25 Public High School Tangerang by paying full attention to the specifications and criteria in terms of the character and performance of teachers and their employees. Strategic efforts to maintain and enhance school quality management have shifte the approach from being reactive to a systematic and planned one. The key step in Human Resource (HR) development planning is the establishment of a school Development Team, wich functions as the primary deiving engine that transforms evaluation data into targeted capacity-building programs. This ensures that improvements in staff qualifications and competencies are aligned with the overall goals of enhacing educational quality. Quality assurance is conducted through accreditation, internal and external evaluations, student assesments, as well as on goingmonitoring and feedback. Through this school development team mechanism, Human Resource (HR) development planning is designed to be both fulfilled and optimized.